Gender in Gambling Research or Gender Research in Gambling? An Intersectional Socio-Constructionist Approach - Kairouz, Sylvia; Sowad, Abu Saleh Mohammad; Lambo, Lesley; Saeidzadeh, Zara; Morvannou, Adèle (Critical Gambling Studies, 2026)
A scoping review by Kairouz et al. (2023) on the conceptualization of gender in peer-reviewed gambling scholarship (2000–2020) found that only 58 of 2,532 articles addressed gender as a sociocultural construct. Building on that review, this paper examines how these 58 studies discuss gender as a sociocultural construct. Using a feminist social constructionist lens, we analyzed gambling practices and gamblers' experiences to understand how gender is represented and theorized. Through thematic content analysis, we discovered that only 39 of the 58 articles use sociocultural conceptualizations of gender when discussing gamblers' identities and lived experiences. Our analysis identifies three dominant themes illustrating how gender is constructed in gambling research: gender binary roles, men's domination, and gambling-related harms against women. While feminist qualitative research in gambling studies is growing, we argue that gender-focused scholarship remains constrained by binary frameworks, limited intersectional engagement, and insufficient attention to structural inequalities. Consequently, gambling research tends to reproduce unequal gendered power relations while overlooking the broader social factors shaping gamblers' experiences. We call for more nuanced analyses of gendered social relations, at intersections with sexuality, class, race, ethnicity, nationality, age, and (dis)ability to develop more effective measures for harm prevention and support.